Traduire ensemble pour faire résonner les voix de la marge - Czubińska, Małgorzata (Studia Romanica Posnaniensia, 2024)
Although the history of translation and its iconography mostly convey to us a vision of translation as an individual and solitary activity (Monti, 2018, p. 9), in Canada, which is officially bilingual and multicultural at the federal level, the practice of literary translation has recently increasingly taken collective forms. In the following paper, the analysis will be based on two examples of a collaboration between literary translator Arianne Des Rochers with Natasha Kanapé-Fontaine (for the book Islands of Decolonial Love/Cartographie de l’amour décolonial) and with Édith Bélanger (for the book A Short History of the Blockade/Une brève histoire des barricades), the two works written in English by Leanne Betasamosake Simpson, a leading figure in Canada’s Aboriginal resurgence.